Weed infestation in canopy of spring barley in condition of different tillage systems and fertilization and plant protection levels - Piotr Kraska (Acta Agrobotanica, 2012)
The purpose of this work was to determine the influence of conventional tillage (fall ploughing at 25 cm) and minimum tillage systems (chisel ploughing at 30 cm) and two differentiated fertilization and plant protection levels on number, species composition and air dry weed mass in spring barley cv. Rataj. This spring barley was cultivated in crop rotation potato - spring barley - winter rye. The analysis of field infestation was made prior to spring barley harvest with quantitative- weighting method. There was estimated number of weeds, weed species composition and air dry weight of weeds in two randomly chosen areas of each plot of 0.5 m2. The density of weeds and weed air dry weight was statistically analysed by means of variance analysis, and the mean values were estimated with Tukey's confidence intervals (p=0.05). Intensive level of fertilization and chemical crop protection decreased number of monocotyledonous weeds and total weeds in canopy of spring barley. Conventional system of soil cultivation decreased in a canopy of spring barley the following species of weeds: Geranium pusillum, Galinsoga parviflora, Stellaria media, Apera spica-venti, Poa annua and Echinochloa crusgalli. Conventional tillage increases number of Chamomilla suaveolens and Fallopia convolvulus in a canopy of spring barley. Intensive fertilization and plant protection levels decreased weed infestation first of all through Echinochloa crusgalli, Apera spica-venti, Fallopia convolvulus, Galinsoga parviflora, Geranium pusillum, Chenopodium album and Setaria pumila.